Resposta à Juliette Simont - André Christian Dalpicolo (Princípios, 2005)
The objective of this work is to reveal how the Belgian researcher Juliette Simont confered a different interpretation in respect to the undestanding of the alienation phenomenon in the corpus sartrianum, once she related it to a kind of “obligation” that the human condition must accept in its temporal development. Better: she identifies this phenomenon with the exteriority produced in the man’s attempt to surpass the finity that surrounds him. Therefore, Juliette concludes that the ethical issue remains unsolved in Sartre’s thought, because it is impossible to imagine the development of human freedom apart from the alienation as “determinism”. In our view, the origin of this different interpretation is based on the explanation related to the influence practiced by Hegel on Sartre, although the latter points out the hypothetical character of the reduction of “Being”. The result is that the essential ethical problem of the corpus sartrianum is not highlighted, as the Belgian researcher never inquires if the man must conduct himself in favour of a “intention moral” or of a “result moral”.